The Importance of Determining Inflammatory Parameters in Patients with Coronary Artery Disease and Type 2 Diabetes Mellitus - Damnjanović, Goran; Đinđić, Boris (Medical Word, 2026)
Inflammation a key factor in the initiation and progression of atherosclerosis. However, the characteristics of the inflammatory process in diabetes are not well understood. Given the importance of inflammation in atherosclerosis as the main etiopathogenetic mechanism of coronary artery disease, the aim of this study was to determine the significance of specific inflammatory parameters in coronary patients with type 2 diabetes mellitus. The study included 40 patients with confirmed coronary artery disease (CAD) and type 2 diabetes mellitus (DM), 30 patients with CAD and 20 control subjects without evidence of CAD, type 2 DM or glucose intolerance. The blood samples were analyzed prior to therapy and the following parameters were determined: the leukocyte count, the high-sensitivity C-reactive protein (hsCRP) levels, and the concentration of albumin and the adhesion molecules ICAM-1 and VCAM-1. The patients with DM had a significantly higher leukocyte count (p < 0.05), elevated hsCRP levels and a higher VCAM-1 and ICAM-1 concentration (p < 0.05), while the patients without DM had less favorable fibrinogen profiles (p < 0.05). The patients with CAD showed significantly higher hsCRP and ICAM-1 concentrations (p < 0.01), as well as VCAM-1 concentrations (p < 0.05). The regression model indicates that elevated albumin concentrations have a significant prognostic value for the occurrence of CAD. The leukocyte count and concentrations of hsCRP, VCAM-1 and ICAM-1 is significantly higher in CAD patients with type 2 DM (p < 0.05). Fibrinogen concentrations is significantly lower in these patients compared to those without type 2 DM (p < 0.05). Inflammatory markers in patients with CAD and type 2 DM may have diagnostic and prognostic significance in the pathogenesis of the disease, and this insight could lead to new approaches in the treatment of coronary patients with type 2 diabetes mellitus.
Keywords: inflammatory parameters; coronary artery disease; diabetes mellitus